Orthopedic consequences of modern gladiators: a systematic review of lower extremity musculoskeletal issues in retired NFL players - McClure, M.; Cooke, B.; Elphingstone, J.; Schick, S.; Paul, K.; Jardaly, A.; Ponce, B. (The Physician and Sportsmedicine, 2023)
Objectives The stressors that National Football League (NFL) athletes face are well-described and documented with regard to multisystem afflictions and injury prevalence. However, the majority of literature discusses the short-term effects rather than long-term outcomes of playing professional football. The purpose of this study was to characterize the long-term musculoskeletal issues in the retired NFL population.